Caracterização de microalgas e cianobactérias: abordagens ecofisiológica e biotecnológica - Silva, Jaqueline Carmo da (Universidade Federal de São Carlos, 2022)
Microalgae are photosynthetic organisms, generally fast-growing, with simple nutritional requirements and physiological plasticity. They produce biomolecules in great variety and many with high added value. Compared to the number of known species, few are commercially used and described in relation to their biochemical composition. This research aimed to investigate the physiology of microalgae with a biotechnological approach. We started the study by investigating 12 strains, including organisms from the Bacillariophyta, Cyanobacteria, and Chlorophyta groups, and a strain chosen to be subjected to biochemical manipulation. CO2 fixation was quantified to associate microalgae productivity with the reduction of important greenhouse gas. Algae were grown in a high-performance cylindrical photobioreactor (PBR) with internal lighting in batch mode under controlled conditions. As a physiological response, growth, and photosynthesis parameters (PhytoPAM), biomolecules (carbohydrates, proteins, lipids total, fatty acid composition, chlorophyll a, and carotenoids), and antioxidant potential were evaluated. We complement the study with an analysis of the biomass by Fourier transform infrared spectroscopy (FTIR) and thermogravimetry (TG). The results showed that Desmodesmus spinosus had the highest yield of algal biomass (2.4 g L-1), in addition to presenting high levels of chlorophyll a, and total carotenoids, as well as Monoraphidium indicum. As for the fatty acid composition, Nannochloropsis gaditana stood out in the production of eicosapentaenoic acid (EPA). However, Kirchneriella aperta stood out in the parameters: antioxidant activity (69%), protein and carbohydrate content, photosynthetic rates (~0.80), and a higher rate of CO2 fixation. FTIR showed that the species with the highest lipid content were in Chlorophyta N. gaditana, K. aperta, M. indicum, Chlorolobion guanense, and Ankistrodesmus densus. TG showed 3 stages of thermal decomposition for all species. The microalgae K. aperta was selected for the study of biochemical manipulation. In it, the alga was exposed to different colors of light and copper concentration, alone and in combination. We showed that copper and isolated light colors resulted in higher concentrations of biomolecules compared to the combined factors and the control. Finally, a large-scale test (250 L) using the microalgae Chlorella fusca was carried out in a raceway reactor maintained in an oven. Developed in Spain, this study showed that real-time monitoring of photosynthesis showed rETR values twice as high compared to spot analysis performed in the laboratory. In addition, the microalgae C. fusca showed high concentrations of photoprotective compounds. The present results provide relevant information on the physiology, photosynthesis, and biochemical characterization of different microalgae and highlight potential species for further investigation with the aim of commercial applications.
Characterization of microalgae and cyanobacteria: ecophysiological and biotechnological approaches
Keywords: Bioprospecção; Microalgas; Composição bioquímica; Fotossíntese; Bioprospecting; Microalgae; Biochemical composition; Photosynthesis; CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA